Cambios en las representaciones sociales sobre las drogas y sus usuarios en la sociedad española - María de la Villa Moral Jiménez (Escola de Enfermagem de Ribeirão Preto da Universidade de São Paulo, 2007)
Social representations on the experience of young people with psychoactive substances are described, as well as changes in the dominant tendencies on the risks associated with alcohol consumption in the Mediterranean culture and other drugs, such as derivatives of cannabis or psycho stimulants. This study proposes, as a preventive, psychosocial and socio-communitarian intervention strategy, to work on the reflection of social representations and the dominant discourse on drugs in order to redimension the consequences of the experience with psychoactive substances, to increase risk perceptions and to promote changes in attitudes, with a view to a positive and healthy tendency at the global level.